Integrated Education in Conflicted Societies - McGlynn, Claire; Zembylas, Michalinos; Bekerman, Zvi.; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
Academics and practitioners examine the developing field of integrated education in conflicted societies, where children who would normally be educated apart are deliberately educated together. They draw on a range of theoretical and practical frameworks, providing numerous case studies from Northern Ireland, Israel, Macedonia, and Cyprus.
Keywords: Education; International relations; International education; Comparative education; School management and organization; School administration; Educational policy; ducation and state; Social sciences; Education; International and Comparative Education; Social Sciences, general; Educational Policy and Politics; Administration, Organization and Leadership; International Relations